Amazon Fund: financing deforestation avoidance - Jacques Marcovitch; Vanessa Cuzziol Pinsky (RAUSP: Revista de Administração da Universidade de São Paulo, 2014)
The Amazon Fund, created in 2008 by the Brazilian Federal Government, is managed by Banco Nacional de Desenvolvimento Econômico e Social (BNDES). It is a pioneering initiative to fundraise and manage financial resources to cut back deforestation and support sustainable development for 30 million inhabitants in the Amazon Biome. The Amazon Fund has already received more than R$ 1.7 billion in grants (about USD 787 million). This essay analyzes the Amazon Fund's governance and management with focus on its operation and from its stakeholders' perspectives. A combination of research methods includes: documental research, in-depth interviews, and speech analysis. The study offers a comparative analysis of strengths and weaknesses related to its governance. Furthermore, it proposes ways to improve its management towards greater effectiveness. The essay also includes an assessment of the government of Norway, a major donor to the fund. The governments of Norway and Germany, in partnership with Brazil, reveal how important it is to experiment with new means of international cooperation to successfully reduce greenhouse gas emissions through rainforest preservation.